1994
DOI: 10.1346/ccmn.1994.0420511
|View full text |Cite
|
Sign up to set email alerts
|

Palagonite Reconsidered: Paracrystalline Illite-Smectites From Regoliths on Basic Pyroclastics

Abstract: Abstract--Poorly crystalline authigenic alteration products of basic pyroclastics from the Golan Heights, Israel, were investigated by XRD, DTA, TGA, FTIR and chemical analysis. Modeling XRD patterns with the use of NEWMOD code provided a way to identify these clays as random interstratified illite/ smectites (I/S) with ~ 70% ofillitic interlayers. Their characteristic features were very poor basal reflections, distinct hk bands, high CEC and low (-2%) I(20 content. Crystallite thickness distribution was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 26 publications
2
15
1
Order By: Relevance
“…The range of CEC of palagonitized glass we determined by the in situ method (30 to 60 meq/100 g) is generally lower than that determined by conventional methods reported in previous studies (for example, Singer (1974) and Berkgaut et al (1994) reported 60 to 100 meq/100 g). However, the conventional measurements reported in the literature were done on bulk "palagonite," which typically contains layer silicates of a presumably higher CEC than the palagonitized glass itself.…”
Section: Cec Of Layer Silicates and Palagonitized Glasscontrasting
confidence: 79%
See 2 more Smart Citations
“…The range of CEC of palagonitized glass we determined by the in situ method (30 to 60 meq/100 g) is generally lower than that determined by conventional methods reported in previous studies (for example, Singer (1974) and Berkgaut et al (1994) reported 60 to 100 meq/100 g). However, the conventional measurements reported in the literature were done on bulk "palagonite," which typically contains layer silicates of a presumably higher CEC than the palagonitized glass itself.…”
Section: Cec Of Layer Silicates and Palagonitized Glasscontrasting
confidence: 79%
“…Since the bulk clay fractions of hyaloclastitic samples contain appreciable palagonitized glass, we also measured its in situ properties. Previous studies (Singer 1974;Berkgaut et al 1994) have shown that "palagonite" has a relatively high CEC (60 to 100 meq/100 g, as measured on bulk clay fractions), although the relative contribution of exchangeable cations from dominantly amorphous material versus crystalline layer silicates has not been previously explored.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Caballero (1985) found that hydrothermal solutions of granitic composition favored smectite formarion, and McDaniel et al (1995) reported beidellite from tephra in the presence of water with low pH and with organic metal-complexing agents. Berkgaut et al (1994) found illite-smectite (I-S) in soils developed on pyroclasrics where there was an alternation of humid and dry seasons. Halloysite and kaolinite dominate in a humid climate in soils formed form volcanic ash and pumice (Wada, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Its formation has been attributed to induce leaching by rainwater during the cyclic alternation of wet and dry seasons [4].…”
Section: Introductionmentioning
confidence: 99%